América Latina '96 en el Museo Nacional de Bellas Artes : con el auspicio de Citibank. - Bermúdez, Jorge A.; Chávez, Jorge Villacorta; Conde, Teresa del; Glusberg, Jorge; Herkenhoff, Paulo; Kalenberg, Angel; Manrique, Jorge Alberto; Mellado, Justo Pastor; O'Donnell, Mario; Palomero, Federica; Roca, José Ignacio; Sierra, Alberto (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1996)
Agois, Mariella ; Altamirano, Carlos ; Barreto, Lia Menna ; Barrios, Alvaro ; Borges, Jacobo ; Chacón, Sigfredo ; Cárdenas, Santiago ; Damiani, Jorge ; Diaz, Gonzalo ; Duclos, Arturo ; Eckell, Ana ; Flores, Irma Palacios ; Garcia, Daniel ; Gomes, Fernanda ; González, Beatriz ; Grieve, Alberto ; Iturria, Ignacio ; Leñero, José Castro ; Leirner, Nelson ; Macotela, Gabriel ; Mirocznyk, Gabriel Martín ; Navarro, Gilberto Aceves ; Neuenschwander, Rivane ; Ramos, Nelson ; Rojas, Miguel Angel ; Siquier, Pablo ; Smith, Courtney ; Testa, Clorindo ; Urbieta, Jesús ; Wiesse, Ricardo ; Zerpa, Carlos
biografie
Spaans
boek
Keywords: Argentinië; Brazilië; Chili; Latijns Amerika; Mexico; Peru; Uruguay; Venezuela